Features of students’ perceptions of urban graffiti with significant educational potential - O. V. Kruzhkova; M. R. Babikova; S. D. Robin (Образование и наука)
Introduction. In a modern urban environment, graffiti also plays a role in shaping the younger generation. Certain creolised texts have a significant educational potential as they reach a wide audience of casual observers. These texts can propagate, emphasise, appeal to, or influence the emotional state of the reader. However, the peculiarities of perception and assessment of the educational potential of urban graffiti are practically unstudied in the scientific community. Aim. The aim of the study was to investigate the mechanism of the impact of urban graffiti with pronounced educational potential on individuals by assessing the features of their perception, memorisation, emotional response, and interpretation of the content. Methodology and research methods. The present study is part of an exploratory laboratory experiment using high-precision research equipment, known as an “eye-tracker”. During the laboratory experiment, the perception features of 21 texts were evaluated. These texts were selected from a pool of 2,000 photographs, which were taken of texts vandalised in the megacities of the Russian Federation. The results were processed mathematically and statistically using descriptive statistics, MANOVA, comparative analysis, and contingency tables. Results. The results of the study demonstrate that urban graffiti with educational potential is memorised and reproduced by 10 to 43% of the study participants. The study describes the unique eye-movement patterns observed during the perception of creolised texts, which lead to a reduced comprehension of the educational content and impact embedded in them. Generalised principles for creating urban graffiti that effectively realise positive educational potential include the presence of a prosocial message, brevity of the text, literal and unambiguous communication, complementation of the text with a consistent graphic image, and the use of creolised text. Scientific novelty. The scientific novelty lies in identifying the mechanism through which urban graffiti, with significant educational potential, impacts students. This is achieved by characterising their perception, emotional evaluation, and interpretation. Practical significance lies in the potential use of the collected data to achieve educational goals through the utilisation of street art and graffiti in urban spaces. This includes considering the specific characteristics and limitations in how young people perceive the educational value of these art forms.